Fundamental of entrepreneurship (ENT 300) Noba / Amirul Hafizin Nazrin... [et al.] - Nazrin, Amirul Hafizin; Azmi, Nur Amin Abdul Rahman; Zulkifly, Zulfikri; Ibrahim, Ahmad Harith (2011)
The company starts from a simple idea where art should be done with meaning which is why the name of our company is NOBA or “not only blank art” by the founder and formed by the five shareholders. Our company main activities are selling printed products such as t shirts, shoes and etc. Besides that, our company also provide an offer for the client to make their desired design through discussion and other processes to get what the client wants. The shareholders in this company will have the responsibility to make sure the company business run smoothly according to their position such as general manager, administer, marketing manager, operation manager, and financial manager. The shareholders of NOBA are Amirul Hafizin Bin Nazrin as The General Manager and The Administer, Nur Amin Abdul Rahman Bin Azmi as The Marketing Manager, Zulfikri Bin Zulkifly as The Operational Manager, and Ahmad Harith Bin Ibrahim as The Financial Manager.